A 3D MHD simulation of SN 1006: a polarized emission study for the turbulent case - Velazquez, Paula Florencia (2017)
Three dimensional magnetohydrodynamical simulations were carried out in order to perform a new polarization study of the radio emission of the supernova remnant SN 1006. These simulations consider that the remnant expands into a turbulent interstellar medium (including both magnetic field and figuredensity perturbations). Based on the referenced-polar angle technique, a statistical study was done on observational and numerical magnetic field positionangle distributions. Our results show that a turbulent medium with an adiabatic index of 1.3 can reproduce the polarization properties of the SN 1006 remnant. This statistical study reveals itself as a useful tool for obtaining the orientation of the ambient magnetic field, previous to be swept up by the main supernova remnant shock.